2013
DOI: 10.1007/s12223-013-0232-z
|View full text |Cite
|
Sign up to set email alerts
|

The persistence of biofilm-associated antibiotic resistance of Staphylococcus aureus isolated from clinical bovine mastitis cases in Australia

Abstract: The aim of this investigation was to determine the persistence of biofilm-associated antibiotic resistance developed by methicillin-sensitive Staphylococcus aureus (MSSA), of different capsular types, during biofilm formation. Because of superiority of the tissue culture plate (TCP) over the Congo Red Agar (CRA) method for measuring biofilm formation, it was used to determine the persistence of the antibiotic resistance developed by the isolates in biofilms. The antibiotic resistance was found to persist for 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 96 publications
3
29
0
1
Order By: Relevance
“…The presence of cap genes in all of the isolates analysed was also reported in the studies conducted by Tollersrud et al (2000); Salasia et al (2004); Bardiau et al (2014), and Khichar and Kataria (2014), with S. aureus isolated from bovine mastitis, as well as by Verdier et al (2007), with S. aureus isolated from human infections. Nevertheless, Reinoso et al (2008) and Camussone et al (2012) in Argentina, Babra et al (2013) in Australia and Marques et al (2013) in Brazil reported lower percentages of S. aureus isolates collected from bovine mastitis samples carrying the cap gene.…”
Section: Polysaccharide Productionmentioning
confidence: 88%
See 1 more Smart Citation
“…The presence of cap genes in all of the isolates analysed was also reported in the studies conducted by Tollersrud et al (2000); Salasia et al (2004); Bardiau et al (2014), and Khichar and Kataria (2014), with S. aureus isolated from bovine mastitis, as well as by Verdier et al (2007), with S. aureus isolated from human infections. Nevertheless, Reinoso et al (2008) and Camussone et al (2012) in Argentina, Babra et al (2013) in Australia and Marques et al (2013) in Brazil reported lower percentages of S. aureus isolates collected from bovine mastitis samples carrying the cap gene.…”
Section: Polysaccharide Productionmentioning
confidence: 88%
“…A higher proportion of cap5 isolates (compared to cap8 isolates) has also been reported by Salasia et al (2004) in Indonesia, Reinoso et al (2008) and Camussone et al (2012) in Argentina, and Khichar and Kataria (2014) in India. Other studies conducted in different countries reported that cap5 and cap8 were evenly distributed among S. aureus isolates from bovine mastitis (Bar-Gal et al 2015) or that there was a higher proportion of cap8 than cap5 isolates (Salasia et al 2004;Babra et al 2013;Marques et al 2013;Bardiau et al 2014).…”
Section: Polysaccharide Productionmentioning
confidence: 94%
“…Bovine mastitis is a major disease affecting dairy cattle worldwide and is a costly disease for dairy producers [22]. But in recent years, conventional methods have frequently been unable to prevent intramammary infection, antibiotics are not very effective in the treatment of mastitis and have a negative impact on human health [23]. Mammary epithelial cells, the most numerous cells in the mammary gland, are parts of the functional unit of the udder, which are responsible for the synthesis of many components in milk that provide nutritional and immunological support to the offspring [24].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics are applied near the end of lactation [141] and may persist in the udder in high concentrations to destroy pathogenic bacteria for 20-70 days. The applied antibiotic has enhanced penetration capacity because of long time contact and curing intramammary infections unless resistance to novel antibiotics is developed by the entering pathogen [142]. Dry cow therapy has been described to remove nearly 100% of mastitis caused by S. agalactiae [139,143].…”
Section: Dry Cow Therapymentioning
confidence: 99%